The Effect of Tempol Administration on the Aortic Contractile Responses in Rat Preeclampsia Model. (3rd September 2012) - Talebianpoor, Mohammad Sharif; Mirkhani, Hossein
Abstract : It is reported that reactive oxygen species production has a critical role in the manifestations and complications of preeclampsia. In the present study, the effect of tempol on the response changes of aortic rings of preeclamptic rats has been studied. Preeclamptic rats (induced by L-NAME) were treated with three different oral doses of tempol (20, 60 and 180 mg/kg/day) from the Day 10 of gestation. Systolic blood pressure, plasma malondialdehyde and 8-isoprostane and the vascular effects of phenylephrine, calcium, acetylcholine and diazoxide were the studied parameters. L-NAME administration resulted in hypertension, proteinuria, increased oxidative stress markers, increased vascular sensitivity to phenylephrine and decreased sensitivity to acetylcholine in pregnant rats. No significant changes in response to calcium and diazoxide were observed. Tempol at doses of 20 and 60 mg/kg/day significantly reversed these changes but at a high dose (180 mg/kg/day), it had no significant effect and in some cases intensified the effect. These results revealed that in the experimental preeclampsia, the sensitivity of rat aorta to alpha- adrenergic receptor agonists was increased and its endothelium-dependent relaxation was decreased. Tempol at lower used doses reduced the blood pressure and oxidative stress and restored the normal responsiveness of vascular tissue in preeclamptic rats.